Conversion of rice husks to polyhydroxyalkanoates (PHA) via a three‐step process: optimized alkaline pretreatment, enzymatic hydrolysis, and biosynthesis by Burkholderia cepacia USM (JCM 15050). Issue 1 (3rd May 2016) - Heng, King‐Sern; Hatti‐Kaul, Rajni; Adam, Farook; Fukui, Toshiaki; Sudesh, Kumar
Abstract: BACKGROUND: Rice husks (RH) are agricultural residues with abundant storage of cellulose and hemicellulose, making them a potential feedstock for polyhydroxyalkanoate (PHA) production. In this study, optimization of pretreatment with alkali under various conditions was performed before enzymatic hydrolysis using Celluclast 1.5 L (EC 3.2.1.4) and Novozyme 188 (EC 3.2.1.21). The hydrolysate was fed to two strains, Burkholderia cepacia USM (JCM 15050) and Cupriavidus necator NSDG‐GG, an engineered strain of Cupriavidus necator H16, to evaluate their PHA production. RESULTS: Pretreatment of RH using 1.0 mol L −1 potassium hydroxide (KOH) at high temperature and pressure (HTP) (121 °C, 0.1 MPa) gave maximum sugar yield of up to 87% (per total carbohydrate content) after optimized enzymatic hydrolysis, whereby the undiluted hydrolysate contained approximately 20 g L −1 total reducing sugars (TRS). B. cepacia USM utilized the hydrolysate more efficiently compared with C. necator NSDG‐GG, with a maximum cell dry weight (CDW) of 4.9 g L −1 and 40 wt% PHA at shake‐flask scale. The CDW and PHA content of B. cepacia USM cultivated in a 5 L fermentor were 7.8 g L −1 and 50%, respectively. The decrease in total phenolics at the end of fermentation suggested that B. cepacia USM was able to metabolize phenolic compounds. CONCLUSION: Through optimized alkali pretreatment and enzymatic hydrolysis, RH has the potential to be converted to PHA by B. cepacia USM, thus valorizing this agricultural by‐product. © 2016 Society of Chemical Industry